Determinantes sociais da Tuberculose associados ao estrato de pobreza no Brasil no período de 2014 a 2017 - Campos, Barbara Almeida (2022)
It is estimated that more than 10 million people had TB in the year. One of the biggest problems present for the eradication of the disease is poverty. Objective: to analyze the social determinants of TB associated with the poverty stratum in Brazil from 2014 to 2017. Methodology: This is a cohort study using a quantitative method, carried out in seven Brazilian capitals, between 2013 and 2014 Results: Yellow, indigenous and unemployed individuals were more likely to be considered extremely poor. Individuals aged 21-29, yellow and indigenous, up to 8 years of schooling, unemployed, retired, students and alcoholics were more likely to be considered poor. Conclusion: With regard to social determinants, it is important to strengthen social security policies for TB patients.